Effect of Hyaluronic Acid/Carboxymethylcellulose and Flunixin Meglumine Combination on the Prevention of Postoperative Intraabdominal Adhesions: An Experimental Study in Rabbits - Kom, Mustafa (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
Despite the development in the knowledge concerning pathophysiology of abdominal cavity and improvement in surgical techniques, intraabdominal adhesions are one of the most common complications in surgery. The aim of this study was to determine the effects of hyaluronic acid/carboxymethylcellulose (HA/CMC) and flunixin meglumine combination on the prevention of postoperative intraabdominal adhesions in rabbits. All the surgery were made under aseptic condition under general anesthesia. A 2x2 cm area of parietal peritoneum was resected on the abdominal wall after median laparotomy. Twenty-four adult, male rabbits were divided into four groups equally. Groups were evaluated as C (control), S (HA/CMC), F (flunixin meglumine), and SF (HA/CMC and flunixin meglumine combination). No medication was given to the rabbits in group C. In S and SF groups, 3x3 cm of HA/CMC applied directly to peritoneal defect. In F and SF groups, flunixin meglumine was administred 1.1 mg/kg for 5 days intraperitoneally. Relaparotomy was performed 10 days after surgery. As a result of macroscopical and histopathological evaluations, the scores of adhesion in the S, F, and SF groups were significantly lower than those of the control group (P<0.05). Adhesion scores in SF group were lower as compared to S and F groups (P<0.05). It is observed that HA/CMC and flunixin meglumine combination can be used more effective on the prevention of postoperative intraabdominal adhesions in rabbits.
Postoperatif İntraabdominal adezyonların önlenmesinde hyaluronik asit/karboksimetilselüloz ve fluniksin meglumin kombinasyonu'nun etkisi: Tavşanlarda deneysel bir çalışma
Keywords: Intraabdominal adhesion; Hyaluronic acid/carboxymethylcellulose; Flunixin meglumine; Rabbit